THU0390 Effect of Glucocorticoid Treatment on Wnt Signalling Antagonists (Sclerostin and Dkk-1) and their Relationship to Bone Turnover and Bone Mass. (23rd January 2014) - Gifre, L.; Peris, P.; Ruiz-Gaspà, S.; Monegal, A.; Nomdedeu, B.; Guañabens, N.
Abstract : Background: Wnt-ß-catenin signalling and its antagonists (sclerostin and Dkk-1) play an important role in the regulation of bone mass and osteoblastogenesis. Glucocorticoid therapy (GCCT) is a well known factor related to decreased bone formation and osteoporosis development. Objectives: To analyze the effect of GCCT on Wnt signalling antagonists (sclerostin and Dkk-1) and their relationship to bone mass and bone turnover. Methods: 22 patients (11M/11F, aged 48±20 yrs) recently initiating GCCT were prospectively included (≥7.5mg/day, ≤6months), excluding patients with associated metabolic bone diseases or on antiosteoporotic treatment. Bone turnover markers (Bone formation: P1NP, bone AP; Bone resorption: sCTx), Wnt antagonists (serum sclerostin and Dkk-1, determined by ELISA, Biomedica Gruppe, Austria) were assessed in all patients (at baseline and 12 months). Bone mineral density (BMD) was performed to assess osteoporosis. The results were compared with 20 healthy controls. Results: The mean daily GCCT dose was 66±16 mg/day. Idiopathic thrombocytopenic purpura (73%) and hemolytic anemia (14%) were the most frequently associated conditions. Patients on GCCT showed a significant decrease in bone formation markers versus controls (PINP: 19.6±9.4 vs. 44.1±8.9 ng/ml, p=0.001) and increased bone resorption (sCTx: 0.58±0.23 vs. 0.4±0.17 ng/mL, p=0.049). Patients on GCCT had decreased Dkk-1 compared to controls (31.8±28.1 vs. 46.8±15.3 pmol/L, p=0.028) with similar sclerostin values (39.7±21.3 vs. 32.9±19.3 pmol/L, p=0.399). 20% had densitometric osteoporosis. Sclerostin correlated positively with GCCT doses (r=0.505, p=0.016) and lumbar BMD (r=0.554, p=0.008), and negatively with bone AP (r=-0.510, p=0.015). At 12 months, Dkk-1 significantly decreased compared to baseline (16.6±13.8, p=0.02), and sclerostin tended to increase (49.2±12.0, p=0.496). Conclusions: The effect of GCCT on the serum levels of the Wnt signalling parameters differs depending on the antagonist evaluated. Dkk-1 levels decreased after the initiation of GCCT whereas sclerostin values tended to increase and showed a relationship to the dose of GCC and bone formation parameters. Acknowledgements: Work funded by a grant from Societat Catalana de Reumatologia. Disclosure of Interest: None Declared